Surface modification of HSLA steel and its fracture behavior - Abdullrhman Hossin, Musa; Maleque, Md. Abdul; Ali, Mohammad Yeakub (2016)
The use of a tungsten inert gas (TIG) welding torch process has resulted in the development of an economical route for surface engineering of alloys known as surface modification giving similar results to the more expensive high power laser process. Due to the preheating generated by this process, the extent of the temperature rise is sufficient to produce significant changes to the preplaced high melting point powders on the surface in terms of microstructure and mechanical properties. In this present study, the surface of high strength low alloy (HSLA) steel was surface modified with the preplacement of pure Titanium (Ti) powder using a tungsten inert gas (TIG) arc heat source, at 100 ampere current with a voltage 30 V and a constant traversing speed of 1.0 mm/s using Argon shielded gas. The effect of preplaced Ti powder on the strength and toughness properties of the modified HSLA steel surface was investigated. The results indicated that the tensile and yield strength of HSLA steel decreased by ~12% and ~14%, respectively. While the impact toughness increased by ~33% and the ductility decreased by ~50%. The fractography analysis results by scanning electron microscopy (SEM) were also presented in this paper.